Comparison of reduced-order dynamic models of induction machines. - Thiringer, T. (IEEE Transactions on power systems)
The paper deals with the validity of various dynamic models of induction machines. The fifth-order Park model and various reduced-order models are used to predict the low-frequency dynamic response of a 15 kW induction machine, and the theoretical results are compared with an extensive series of measurements. Several transfer functions are investigated in the perturbation frequency region below 35 Hz using three types of basic excitations: perturbations in the shaft torque, supply voltage and supply frequency. The maximum perturbation frequency for an error less than 10% is used to study the validity range of the models; this range is evaluated for each model and transfer function, using the data of 31 different machines. The influence of the machine parameters and various physical phenomena is studied. The results show that a large number of transfer functions is needed for judging the general validity of a dynamic model